Tinjauan Literatur: Model Flipped Classroom dengan Elemen Gamification Untuk Memfasilitasi Emotional Engagement Siswa (Current Research in Education: Conference Series Journal, 2023)
Currently, the quality of Indonesian education is becoming the center of attention ofmany people, one of which is the high order thinking skills (HOTS) of students. HOTSis needed by students to face challenges in certain situations in everyday life. However,based on the results of the PISA score, Indonesia is still categorized as low. This provesthat the HOTS level of most students in Indonesia is still relatively low. Thus,increasing students' HOTS requires learning that can support students' holistic needs, bytrying to increase the effectiveness of student-centered learning, and pay better attentionto aspects of student involvement during classroom learning. The purpose of this studyis to provide literature on the application of the flipped classroom model using elementgamification, to increase student involvement from an emotional involvementperspective. The research method used is a systematic literature review. This researchshows that adding gamification elements into the flipped classroom results in highermotivation, and a better level of emotional involvement of students because learning ismore fun.